1973
DOI: 10.1159/000197477
|View full text |Cite
|
Sign up to set email alerts
|

Exocrine Secretory Responses of the Pancreas to Pentagastrin and to a Meat Meal in Dogs

Abstract: The pancreatic responses of four dogs with pancreatic and gastric fistulae (GF) were studied to intravenous infusion of pentagastrin in doses maximal for gastric acid secretion, and separately to a 400-gramme meat meal. With the GF open a small increase in pancreatic bicarbonate (p < 0.05), and a marked increase in protein output was noted in response to pentagastrin. With the GF closed bicarbonate and protein outputs to pentagastrin (21.5 ± 1.8 SEM/mEq 4 h and 2,305 ± 249 SEM/mg 4 h) were not significantly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1978
1978
1998
1998

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…9) reported that the endogenous releases of secretin and CCK-PZ from intestinal mucosa were inhibited by atropine. Gastrin which is known to be secreted through the cholinergic mechanism10, 11) has been reported to increase the exocrine pancreatic secretion in rats12,13) rabbits14), cats 15.16) and dogs17, 18,19,20,21). Therefore , the possibility is not excluded that decreased secretion of these gastrointestinal hormones by atropine caused at least a part of decreased pancreatic exocrine secretion.…”
Section: Discussionmentioning
confidence: 99%
“…9) reported that the endogenous releases of secretin and CCK-PZ from intestinal mucosa were inhibited by atropine. Gastrin which is known to be secreted through the cholinergic mechanism10, 11) has been reported to increase the exocrine pancreatic secretion in rats12,13) rabbits14), cats 15.16) and dogs17, 18,19,20,21). Therefore , the possibility is not excluded that decreased secretion of these gastrointestinal hormones by atropine caused at least a part of decreased pancreatic exocrine secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Besides food, hormones, such as pentagastrin, can also stimulate the exocrine secretion of the pancreas: directly, resulting in a protein-rich secretion, and indirectly by virtue of their effect on gastric acid secretion and consequently the release of secretin and cholecystokinin when acid gains access to the duodenum (Gupta et al 1973).…”
Section: Composition Of Pancreatic Juicementioning
confidence: 99%
“…Considerable variation has been reported in the response of the pancreas to gastrin depending on the spe cies and experimental conditions .Gastrin stimulated the pancreatic exocrine secretion in dogs5, 6,7,8,9),rats10,11),rabbits12)and pigs13) ,but did not stimulate in cats14)and man 15,16,17)though did in some reports18, 19) .The role of gastrin as a regulator of pancreatic exocrine secretion has not been proved adeauetiv in sheen .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of intravenous injection of pentagastrin on thepancreatic exocrine secretion in sheep was examined comparing with the response to CCK- 8 Marked decrease of pancreatic exocrine secretion induced by intravenous infusion of atropine suggests that the cholinergic mechanisms play a considerable role in th e control of pancreatic exocrine secretion in sheep1) .The release of secretin from intestinal mucosa2)and the action of secretie and CCK-83)to the exocrine pancreas were not depressed by atropine .The release of CCK from intestinal mucosa was ,h owever,inhibited by atropine,indicating that the release of this hormone is greatl y mediated by the cholinergic mechanism3) .While,gastrin which is secreted by cholinergic stimulation from the gastric and intestinal G cell has the simil ar Cterminal portion of CCK4).If gastrine has respectable effect on exocrine pancreas ,the decreased release of gastrin by atropine should be considered as one of th e reasons in great reduction of pancreatic secretion induced by atropine . Considerable variation has been reported in the response of the pancreas to gastrin depending on the spe cies and experimental conditions .Gastrin stimulated the pancreatic exocrine secretion in dogs5, 6,7,8,9),rats10,11),rabbits12)and pigs13) ,but did not stimulate in cats14)and man 15,16,17)though did in some reports18, 19) .The role of gastrin as a regulator of pancreatic exocrine secretion has not been proved adeauetiv in sheen .…”
Section: Introductionmentioning
confidence: 99%